Cyclic Distraction–Compression Dynamization Technique Enhances the Bone Formation During Distraction Osteogenesis - Liu, Yanshi; Cai, Feiyu; Liu, Kai; Liu, Jialin; Zhang, Xiaoxu; Yusufu, Aihemaitijiang (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Interfragmentary movements have benefits in the improvement of bone formation during distraction osteogenesis (DO). Although several clinical studies reported positive outcomes regarding the application of the cyclic distraction-compression (CDC) dynamization technique in cases with poor bone formation during DO, they are mostly anecdotal without a detailed description. The purpose of this study was to investigate the effectiveness and potential mechanism of different amplitude and rate of CDC technique on bone regeneration in a rat femur distraction osteogenesis model. Methods: A total of 60 adult male Sprague-Dawley rats underwent right femoral mid-diaphysis transverse osteotomy and were randomly and evenly divided into Control (no manipulation), Group1 (CDC therapy), Group2 (CDC therapy with larger amplitude), and Group3 (CDC therapy with slower rate) after distraction. The CDC technique was performed during the middle phase of the consolidation period according to the different protocols. Animals were sacrificed after 4 and 6 weeks of consolidation. The process of bone formation was monitored by digital radiographs, and the regenerate bone was evaluated by micro-computed tomography (micro-CT), biomechanical test, and histological analysis. The serum content of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) were measured by enzyme linked immunosorbent assay (ELISA). Results: Bone regeneration after CDC technique was improved significantly during DO. The digital radiograph, micro-CT, histomorphological analysis, and biomechanical evaluation showed better effects regarding volume, continuity, and mechanical properties of the regenerate bone in Group2 and Group3 when compared to Group1. The angiogenic and osteogenic markers were higher expressed in Group2 and Group3 than in Group1 according to the immunohistochemical analysis. As for ELISA, the serum content of HIF-1α and VEGF were also increased after the CDC technique, especially in Group2 and Group3. Conclusion: The cyclic distraction-compression dynamization technique has benefits on the improvement of bone formation during distraction osteogenesis, and the mechanism may be due to the tissue hypoxia activating the HIF pathway followed by the augmentation of osteogenic-angiogenic coupling. Better outcomes may be achieved by moderately increasing the amplitude and slowing down the rate of the CDC technique.